Identification and characterization of a novel tetrapeptide from enzymatic hydrolysates of Baijiu byproduct - Qiang Wu; Changqing Zhong; Guirong Zeng; Xu Zhang; Liping Xiang; Chang Wan; Yougui Yu (Food Science and Human Wellness)
In order to prepare angiotensin I-converting enzyme (ACE) inhibitory peptides, distilled spent grains of Chinese strong-flavor Baijiu were hydrolyzed by alcalase followed by papain under optimized conditions. A superior ACE inhibitory peptide was separated and purified by ultrafiltration and high-performance liquid chromatography (HPLC), and its amino acid sequence was further identified as Gln-Gly-Val-Pro (QGVP) by electrospray mass spectrometry (ESI-MS). QGVP formed 6 hydrogen bonds with the active site of ACE, which is responsible for reducing α-helix structure content of ACE causing subsequent inactivation. Moreover, it showed no significant cytotoxicity toward human umbilical vein endothelial cells (HUVECs), and significantly induced phosphorylation of endothelial nitric oxide synthase (p-eNOS) and decreased endothelin 1 (END1) expression in angiotensin I (Ang I)-treated HUVECs, demonstrating the potential antihypertensive effect. The peptide QGVP hydrolyzed from distilled spent grain proteins of Chinese strong-flavor Baijiu was expected to be used as a food ingredient to prevent or co-treat hypertension with other chemical drugs.